Organización contable y aplicación de indicadores financieros a la empresa JG Computers de la ciudad de Loja, periodo enero-junio 2015 - Recalde Poma, María Belén (2016)
The thesis entitled "ORGANIZATION ACCOUNTING AND IMPLEMENTATION OF FINANCIAL INDICATORS THE COMPANY" JG COMPUTERS "CITY OF LOJA, PERIOD JANUARY - JUNE 2015" is performed basically as a contribution to optimize business management in the financial sector of the company, so that entitles the owner to obtain timely accounting information for decision making. The research was conducted based on the fulfillment of the objectives initially and the needs of the company, primarily theoretical foundations are presented, in practice we proceeded to organize all the source documentation and meet tax obligations to thereby proceed to develop the plan and Accounting Manual based on business needs, then the initial inventory of assets, securities and obligations of the business through physical finding, which was the product for the preparation of State initial Situation was made, it was made the memorandum of operations to proceed to register each of the seats in the Daybook; then continued with the majorization of each of the accounts resulting from the exercise to proceed with the preparation of the Trial Balance, Worksheet, until obtaining financial statements such as: Statement of Financial Position, Income Statement and Statement of Cash flow. It finished the accounting process the application of financial indicators performed well attendants purchase and sale of goods for proper daily record was also developed. 11 In conclusion, the implementation of the accounting design allows organize your business activities, and also control and determine to what extent they are meeting their objectives, and helps the owner to measure the degree of efficiency, performance and optimize resources and in turn know the situation economic - financial situation of the company in order to make sound decisions.